2011
DOI: 10.1021/bm101584c
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Properties of Chitosan−Cellulose Nanocrystal Polyelectrolyte−Macroion Complexes for Drug Delivery Applications

Abstract: This study examines a novel polyelectrolyte-macroion complex (PMC) between chitosan, a cationic polysaccharide, and cellulose nanocrystals (CNCs), anionic, cylindrical nanoparticles, for potential applications in drug delivery. CNCs were prepared by H(2)SO(4) hydrolysis of wood pulp. The formation of PMCs was monitored by turbidimetric titration. In titrations of a chitosan solution with a CNC suspension, the turbidity reached a plateau, but it had a maximum and then decreased when the direction of titration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 51 publications
5
77
0
Order By: Relevance
“…The cellulose nanocrystals were obtained from acid hydrolysis from wood pulp and formed particles from nanometers to micrometers depending on the nanocrystal cellulose/chitosan ratio. 83 Recently, it was demonstrated that nanocrystalline cellulose was capable of binding ionizable water soluble antibiotics tetracycline and doxorubicin. These hydrophilic drugs were rapidly released and this can be controlled by surface modification by binding the cationic surfactant, cetyl trimethylammonium bromide.…”
mentioning
confidence: 99%
“…The cellulose nanocrystals were obtained from acid hydrolysis from wood pulp and formed particles from nanometers to micrometers depending on the nanocrystal cellulose/chitosan ratio. 83 Recently, it was demonstrated that nanocrystalline cellulose was capable of binding ionizable water soluble antibiotics tetracycline and doxorubicin. These hydrophilic drugs were rapidly released and this can be controlled by surface modification by binding the cationic surfactant, cetyl trimethylammonium bromide.…”
mentioning
confidence: 99%
“…Comb-shaped copolymers composed of dextran backbones and cationic poly((2-dimethyl amino)ethyl methacrylate) side chains were subsequently prepared via atom transfer radical polymerization for nonviral gene delivery. Plasmid DNA were loaded into complex nanoparticles (100–150 nm), which had high gene transfection yield, efficient gene delivery ability in different cancer cell lines, especially in MCF-7cells [166]. Similarly to chitosan and dextran, hyaluronic acid (HA) was chemically modified with the 5β-cholanic acid to form self-assembled nanoparticle (200–400 nm) that combine both passive tumor targeting based on the EPR effect and a more specific or active targeting exploiting the affinity of HA towards CD44 [167].…”
Section: Polysaccharide Nanoparticlesmentioning
confidence: 99%
“…Recently, Roman and co-workers have reported the formation of a novel polyelectrolyte-macroion complex (PMC) from chitosan and NCC at different concentrations for potential applications in oral drug delivery [261]. The concentration of NCC in the reaction medium has a strong effect on PMC formation, with higher NCC concentrations resulting in larger or more highly aggregated PMC particles.…”
Section: Functionalization With Polymersmentioning
confidence: 99%